Sharing the Harvest: The Road to Self-Reliance, Report of the National Round Table on Aboriginal Economic Development and Resources - Canada. Royal Commission on Aboriginal Peoples (Minister of Supply and Services Canada, 1993)
The objectives of the National Round Table on Aboriginal Economic Development and Resources were to stimulate discussion of the economic development challenges facing Aboriginal peoples and to elicit suggestions on how these challenges can best be met. The results of the Round Table were to contribute to the formulation of the Royal Commission’s final recommendations. To bring a broad range of perspectives to the discussion, participants included those knowledgeable in economic development and resources issues and those with expertise in the creation and implementation of economic development initiatives benefitting Aboriginal communities — with a balance in terms of gender, age and Aboriginal identification. Economic development issues are very broad-ranging. To help focus discussion, five issue groups or themes were selected, and participants were asked to consider particular questions relating to each of the themes. Discussion papers were commissioned on each of the themes, and a series of examples or models of individual and community enterprise in economic development were presented. --Objectives, p. 1.